Is forestry really more profitable than upland farming? A historic and present day farm level economic comparison of upland sheep farming and forestry in the UK. (February 2018) - Hardaker, Ashley
Abstract: There are currently 3.16 million hectares of woodland cover in the United Kingdom. At a European scale, the UK is one of the countries with the lowest woodland cover, currently extending to only 13% of the total land area of the UK, this is less than half of the European Union (EU) average of 37 per cent. A significant study carried out by Read et al. (2009) identified that UK wide there is a need to increase significantly levels of new planting and forest creation by more than 23, 000 ha each year over the next 40 years if a substantial influence on reversing climate change is to be realised. It is clear that expansion of the total forested area in the UK necessitates the establishment of new woodland and forest cover on farmland which is either owner occupied or rented out. The main barriers to woodland establishment on farmland cited in the literature, include cultural resistance notably a dichotomous view of farming and forestry as being competing land uses; and lack of awareness of the potential economic benefits of woodland. This study intended to provide information that will improve farmers and landowners understanding of the potential economic differences between business as usual (sheep farming) and woodland creation in the uplands of the UK. The aim of this study was to evaluate the bio-economic potentials of temperate upland clear fell forestry systems in the UK over the last 60 years and determine if afforestation of upland farms has historically produced, and will in the future produce better financial outcomes than conventional upland sheep farming. The study used a bio-economic model based on discounted cash flow analysis to compare and evaluate a conventional upland sheep grazing system against a temperate upland forestry system. Historic investments to cease upland sheep grazing and afforest upland farms in the UK based on historic financial budgeting information available to farmers and landowners in 1956, 1976 would not have been an economically viable and profitable land use change compared to continuation of upland sheep grazing in the UK. Historic markets in 1956 and 1976 were not strong enough to render potential forestry investments profitable without a need for grant assistance. Investments to cease upland sheep grazing and afforest upland farms in the UK in 1996 would have been economically viable and profitable land use investment as timber markets alone were strong enough to render potential forestry investment profitable without a need for grant assistance. Without subsidy, investments to switch from upland sheep grazing and afforest upland farms in 2016 would not be an economically viable and profitable land use change. Current day timber markets alone are not strong enough to influence new woodland establishment.